HCV NS5B RdRp mutations and their effects on ligand binding affinity. (4th May 2022) - Emam, Ahmed; Abdellatif, Khaled R. A.; Amin, Noha H.; Elokely, Khaled M.
ABSTRACT: HCV is an RNA virus, which affects millions of people worldwide and it has no available vaccine so far. Because of genetic differences between the six HCV genotypes, the development of a pan-genotypic modulator is challenging. Besides, the emerged genetic mutations led to a significant resistance to currently used HCV drugs. Consequently, the evolution of drug resistance increases the obstacles to develop effective HCV medications. In this study, we report important factors affecting ligand binding to HCV NS5B RNA dependent RNA polymerase (RdRp) of genotype 1b mutant strains. Extensive analysis of protein–ligand interaction profiles leads to the identification of the most important amino acids for ligand recognition including Asn 411, Arg 386, and Tyr 415. At the atomic level, these amino acids interact through their carbon, oxygen, and nitrogen atoms at different extents with ligand functional groups. Mutations that led to replacement of these crucial amino acids may result in loss of ligand affinity. Molecular dynamics simulation studies were conducted to demonstrate the effect of some mutations on ligand recognition.